Smoothing Asymmetric Shocks vs. Redistributionin the Euro Area: A Simple Proposal for Dealingwith Mistrust in the Euro Area - Heikki Oksanen (Center for Economic Studies and ifo Institute (CESifo), 2016)
The euro area will not have a centralised budget and smoothing of country-specific asymmetric shocks via private financial markets will develop only slowly. Mistrust among the governments has caused rigid, even pro-cyclical fiscal policies. Smoothing mechanisms are absent due to the fear that the transfers would develop into permanent redistribution. For removing these deficiencies we propose a transfer mechanism to be managed in periods of seven years so that the cumulative balance of each country is cleared in equal instalments during the subsequent 7-year period. The transfers would smoothen asymmetric shocks and alleviate the rigidity of the fiscal rules.
Keywords: E42; E62; H10; 330; euro; monetary union; smoothing shocks; fiscal transfers; government budget